Analysis of reproducibility and robustness of a human microfluidic four-cell liver acinus microphysiology system (LAMPS). (30th January 2021) - Sakolish, Courtney; Reese, Celeste E.; Luo, Yu-Syuan; Valdiviezo, Alan; Schurdak, Mark E.; Gough, Albert; Taylor, D. Lansing; Chiu, Weihsueh A.; Vernetti, Lawrence A.; Rusyn, Ivan
Abstract: A human microfluidic four-cell liver acinus microphysiology system (LAMPS), was evaluated for reproducibility and robustness as a model for drug pharmacokinetics and toxicology. The model was constructed using primary human hepatocytes or human induced pluripotent stem cell (iPSC)-derived hepatocytes and 3 human cell lines for the endothelial, Kupffer and stellate cells. The model was tested in two laboratories and demonstrated to be reproducible in terms of basal function of hepatocytes, Terfenadine metabolism, and effects of Tolcapone (88 μM), Troglitazone (150 μM), and caffeine (600 μM) over 9 days in culture. Additional experiments compared basal outputs of albumin, urea, lactate dehydrogenase (LDH) and tumor necrosis factor (TNF)α, as well as drug metabolism and toxicity in the LAMPS model, and in 2D cultures seeded with either primary hepatocytes or iPSC-hepatocytes. Further experiments to study the effects of Terfenadine (10 μM), Tolcapone (88 μM), Trovafloxacin (150 μM with or without 1 μg/mL lipopolysaccharide), Troglitazone (28 μM), Rosiglitazone (0.8 μM), Pioglitazone (3 μM), and caffeine (600 μM) were carried out over 10 days. We found that both primary human hepatocytes and iPSC-derived hepatocytes in 3D culture maintained excellent basal liver function and Terfenadine metabolism over 10 days compared the same cells in 2D cultures. In 2D, non-overlay monolayer cultures, both cell types lost hepatocyte phenotypes after 48 h. With respect to drug effects, both cell types demonstrated comparable and more human-relevant effects in LAMPS, as compared to 2D cultures. Overall, these studies show that LAMPS is a robust and reproducible in vitro liver model, comparable in performance when seeded with either primary human hepatocytes or iPSC-derived hepatocytes, and more physiologically and clinically relevant than 2D monolayer cultures.